A Comparison of Therapeutic and Anti-inflammatory Properties of Triamcinolone and Placebo (Vitamin A) in Treatment of Paederus Dermatitis - Seyed Hasan Nikookar; Ahmad Ali Enayati; Seyed Farzad Motevalli Haghi; Behzad Parsi; Mahmoud Fazeli-Dinan (علوم بهداشتی ایران, 2014)
Abstract Background and purpose: Paederus associated dermatitis has always been considered as a health problem in the northern of Iran. Since until now, the traditional method and some corticosteroids have been used in the treatment of Paederus dermatitis (PD) and no comprehensive studies have been carried out on the new method of treatment. Therefore, this study was aimed to compare the anti-inflammatory effects of triamcinolone with placebo in treatment of PD. Materials and Methods: This randomized double-blind clinical trial was performed during 6 months period in the clinics of Sari and Neka, Iran. Experimental group received triamcinolone and control group received placebo. The therapeutic effects of topically applied triamcinolone in 15 dermatitis patients and 15 control subjects were compared. The study subjects were visited in three separate times in the 1st, 7th and 14th day of the treatment. The data were collected in the questionnaire and compared in both groups by introducing the data into SPSS 11 software and analyzed by means of χ 2 test. Results: A total of 15 patients, 10 and 5 cases were undertaken for treatment in the Sari and Neka Townships, respectively. 40% and 50% of the patients from Sari and Neka Townships had lesion size 6-10 cm2, respectively. In this study, 90% and 100% of the patients from Sari and Neka had complete recovery 7 days after treatment, respectively. Statistical analysis indicated a significant difference between the case and control groups (P < 0.05). Conclusion: Insignificant difference was observed for treatment between the patients from the two Townships under study.